2018
DOI: 10.1007/s42044-018-0021-6
|View full text |Cite
|
Sign up to set email alerts
|

A neuro fuzzy approach for the diagnosis of postpartum depression disorder

Abstract: Postpartum depression is a growing public health problem amongst nursing mothers, which is not given much attention in primary health care settings. It is a type of depression experienced after childbirth that affects an estimated 13-19% of nursing mothers. Postpartum depression is very difficult to diagnose and by concentrating on somatic illnesses, most medical practitioners frequently fail to recognize it. In this paper an Adaptive Neuro Fuzzy Inference System was utilized to predict postpartum depression. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“… Heart disease is one of the most common chronic diseases and causes of adult death worldwide [ 33 ]. Health, Medical Education Department has announced that 33–38 percent of deaths in the country are due to cardiovascular disease, and Iran has the highest rate of heart death in the world.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… Heart disease is one of the most common chronic diseases and causes of adult death worldwide [ 33 ]. Health, Medical Education Department has announced that 33–38 percent of deaths in the country are due to cardiovascular disease, and Iran has the highest rate of heart death in the world.…”
Section: Resultsmentioning
confidence: 99%
“…In 2020, Verma et al [ 32 ] proposed a newly proposed method of hybrid feature selection technique for evaluating the performance of base learners, and we find that the reduced data subset performed is higher than the whole data set. Also, Osubor et al [ 33 ] used an adaptive fuzzy neural inference system to predict postpartum depression. Thirty-six data samples were used in model training.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Machine learning techniques have been applied to diagnosing depression but most of the systems designed failed to perform feature selection and extraction on symptoms that consist of the dataset used for a depression diagnosis. This has reduced the classification accuracy of the machine learning algorithm [14,21]. Although researchers have observed that the diagnosis of clinical depression has ignored optimal training, feature selection, and feature extraction [14,21].…”
Section: Introductionmentioning
confidence: 99%
“…This has reduced the classification accuracy of the machine learning algorithm [14,21]. Although researchers have observed that the diagnosis of clinical depression has ignored optimal training, feature selection, and feature extraction [14,21]. Therefore, it is imperative to design a model for diagnosing clinical depression, which performs feature selection and extraction on the dataset to be used for training the learning algorithm of the design system.…”
Section: Introductionmentioning
confidence: 99%